2023
DOI: 10.1002/epi4.12723
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and pharmacokinetics of intravenous allopregnanolone with and without midazolam pretreatment in two healthy dogs

Abstract: The neurosteroid allopregnanolone (ALLO) is under investigation as a treatment for benzodiazepine-refractory status epilepticus (SE). Here we assess the cardiopulmonary safety of intravenous ALLO by itself and after a clinically recommended dose of midazolam (MDZ) in two healthy adult beagles. Each dog received ALLO (1 mg/kg, IV), and after a washout period of 2 weeks, the dog was dosed with MDZ (0.2 mg/kg, IV) followed 10 min later by ALLO. Behavioral state, vital signs, arterial blood gasses, blood chemistri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In veterinary medicine, evidence and clinical experience are limited to absent. 68 , 111 , 174 Pharmacological interventions such as IV magnesium 68 and allopregnanolone, 85 , 111 as well as mild hypothermia 53 might provide further antiseizure effects in dogs and cats with super‐refractory SE.…”
Section: What If the Combined Measures With First‐ Second‐ And Third‐...mentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary medicine, evidence and clinical experience are limited to absent. 68 , 111 , 174 Pharmacological interventions such as IV magnesium 68 and allopregnanolone, 85 , 111 as well as mild hypothermia 53 might provide further antiseizure effects in dogs and cats with super‐refractory SE.…”
Section: What If the Combined Measures With First‐ Second‐ And Third‐...mentioning
confidence: 99%
“… 176 Two pharmacokinetic studies in dogs showed a favorable pharmacokinetic and safety profile for allopregnanolone in SE. 85 , 111 Hypothermia decreases excitatory neurotransmitters, calcium‐ and glutamate‐induced excitotoxicity, and cerebral metabolic rate, and normalizes intracranial pressure. 177 , 178 According to a clinical report in dogs, 53 mild hypothermia (36.7‐37.7°C) when combined with ketamine‐dexmedetomidine IV CRI was effective in terminating super‐refractory SE.…”
Section: What If the Combined Measures With First‐ Second‐ And Third‐...mentioning
confidence: 99%